INCREASING ATTITUDE AND BEHAVIOR OF DELAYING PREGNANCY OF THE RISKY BRIDE CANDIDATES THROUGH PRECONCEPTIVE HEALTH EDUCATION - Maretta, Megayana Yessy; Rachmadi, Dedi; Husin, Farid; Widyastuti, Deny Eka; Widyastuti, Desy; Khuzaiyah, Siti; Tayyeb, Muhammad (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: World Health Organization identified some factors of high-risk pregnancy. Health education with booklets can improve individual knowledge, attitudes, and behavior. This study aims to analyze the effect of preconception of health education with booklets on increasing the attitudes and behavior of the risky bride candidates.Method:This quasi-experimental pre-posttest design with control groups study was conducted at 4 Religious Affairs Office in Surakarta with a sample of 60 prospective brides divided into 2 groups and selected by consecutive sampling technique. Attitudes and behavior on delaying pregnancy were measured using an attitude questionnaire and a family planning acceptor card. Data analysis with Fisher's test, Chi Square Test, Z Test.Result: There was an increase in positive attitudes (delaying pregnancy) (36.7%), and there were n=10(33.3%) brides who delayed pregnancy (using contraception) in the group that was given education with a booklet with p <0.05 between the two groups. The group that received education using the booklet had the opportunity to improve attitudes 1.3 times and use contraception 1.45 times compared to the control group.Conclusion: This study concludes that pre-conceptional health education using booklets can be an alternative in increasing the positive attitude and behavior of delaying pregnancy at risky prospective brides.